Proceedings of the 8th Working Conference on Mining Software Repositories 2011
DOI: 10.1145/1985441.1985464
|View full text |Cite
|
Sign up to set email alerts
|

Do time of day and developer experience affect commit bugginess?

Abstract: Modern software is often developed over many years with hundreds of thousands of commits. Commit metadata is a rich source of social characteristics, including the commit's time of day and the experience and commit frequency of its author. The "bugginess" of a commit is also a critical property of that commit. In this paper, we investigate the correlation between a commit's social characteristics and its "bugginess"; such results can be very useful for software developers and software engineering researchers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 27 publications
(33 reference statements)
2
99
0
Order By: Relevance
“…It is surprising to find that there is no correlation between any of the ways we measure experience and the bug seeding ratio. Our intuition and related research (see Eyolfson et al [2]) had made us expect that developers would increase the quality of their code the more they contribute to a project. However, both results could be compatible.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is surprising to find that there is no correlation between any of the ways we measure experience and the bug seeding ratio. Our intuition and related research (see Eyolfson et al [2]) had made us expect that developers would increase the quality of their code the more they contribute to a project. However, both results could be compatible.…”
Section: Discussionmentioning
confidence: 84%
“…From a quantitative point of view, experience has been found to be measured in several ways: a) Number of commits [8,7,2]; b) Fixing activity [1]; and, c) Ownership of the source code [3,4].…”
Section: Related Researchmentioning
confidence: 99%
“…Table 7 presents the detailed category of MSR purposes, their detailed task types, and existing approaches. To support Bug-related activity There have been several studies on bug-fix: empirical study on the patterns for bug-fix [58], [155], automatic bugfix [59], [60], understanding the bug-fix patterns of hardware project [61]. Sliwerski et al conducted the empirical analysis about fix-inducing change based on CVS log and BugZilla [58].…”
Section: Data Mining Algorithmsmentioning
confidence: 99%
“…The number of fix-inducing transactions is about three times that of non-fix inducing transactions. Eyolfson et al studied the co-relationship between the patterns of commits and the bugginess for those commits [155]. They explored the Linux Kernel and Postgres-SQL and found several observations: The commits from midnight to 4 A.M were highly possible to be buggy and the commits of everyday committers were less buggy.…”
Section: Purpose Of Msr Analysismentioning
confidence: 99%
“…These studies are helpful to understand the main contributor in a specified domain and assign jobs. In addition, previous studies have researched the correlation between developer experience and code quality [2], [3], [5], [7], but the defect tendency of a developer depends on the file complexity. Other works have suggested that experienced developers are more defect-prone because they often work in the most complex regions [5], [7].…”
Section: Introductionmentioning
confidence: 99%